2010
DOI: 10.1097/mpa.0b013e3181dfcbe5
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Peptidome Profiling of Human Serum for the Detection of Pancreatic Cancer

Abstract: Standardized serum peptidome profiling could be a useful tool to improve biochemical diagnosis of PC in combination with the classic tumor marker, CA 19-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Of the 160 peaks, 16 (10%) features were significantly correlated with the presence of diseases of the pancreas, namely PaCa and ChrPa and only 2 were closely correlated with tumor presence. Interestingly, the finding of an increased frequency of the 2305 m/z feature in PaCa is in line with previous findings made by Zapico-Muñiz et al, 22 who demonstrated an increased peak area for this feature in PaCa, by analyzing samples with MALDI-TOF/MS in positive linear mode. Likewise, 2 (m/z 1865 and 1450) among our first 10 selected most significant features (see Table 1) were also found by the same authors to be significantly correlated with PaCa.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 160 peaks, 16 (10%) features were significantly correlated with the presence of diseases of the pancreas, namely PaCa and ChrPa and only 2 were closely correlated with tumor presence. Interestingly, the finding of an increased frequency of the 2305 m/z feature in PaCa is in line with previous findings made by Zapico-Muñiz et al, 22 who demonstrated an increased peak area for this feature in PaCa, by analyzing samples with MALDI-TOF/MS in positive linear mode. Likewise, 2 (m/z 1865 and 1450) among our first 10 selected most significant features (see Table 1) were also found by the same authors to be significantly correlated with PaCa.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical proteomics has emerged as a promising strategy to develop novel tools for biomarker strategies. [37][38][39][40][41][42] In this study, high-resolution MS profiling of human serum was used, with the aim of detecting specific patterns present in patients with PC. Using this method, a set of seven peptides was found that differentiated PC from healthy volunteers with a sensitivity of 78% and a specificity of 89%.…”
Section: Discussionmentioning
confidence: 99%
“…In the authors' view, the additional application of this peptide strongly improves the diagnostic power of commonly used serum tumour marker panel comprising of CA 19-9 and CEA, which might have additional implication in differential diagnosis of pancreatic cancer and pancreatitis [52]. Similarly, Zapico-Muñiz et al [53] developed standardised protocol to analyse peptidome profiles of human serum for detection of pancreatic cancer. Serum peptides were extracted using immobilized copper ion chromatography followed by MALDI mass spectrometry analysis.…”
Section: Identification Of Biomarkers For Cancer Diagnosismentioning
confidence: 97%
“…The authors reported that the diagnostic sensitivity was 89.9%, and the diagnostic specificity was 92.7%, using two serum features and CA 19-9 serum concentration. By using this approach, the authors were able to distinguish between healthy controls and patients with pancreatic cancer and chronic pancreatitis, with the use of three features of the peptidome (diagnostic sensitivity, 98.2%; diagnostic specificity, 97.1%) [53].…”
Section: Identification Of Biomarkers For Cancer Diagnosismentioning
confidence: 99%